Informal Incentives and Labor Markets - Matthias Fahn; Takeshi Murooka (Institute of Labor Economics (IZA), 2024)
This paper investigates how labor-market tightness affects market outcomes if firms use informal, self-enforcing, agreements to motivate workers. We characterize profit-maximizing equilibria and show that an increase in the supply of homogenous workers can increase wages. Moreover, even though all workers are identical in terms of skills or productivity, profit-maximizing discrimination equilibria exist. There, a group of majority workers are paid higher wages than a group of minority workers, who may even be completely excluded. Minimum wages can reduce such discrimination and increase employment. We discuss how these results relate to empirical evidence on downward wage rigidity, immigration, the gender pay gap, and credentialism.
Keywords: D21; D86; J21; J38; J61; J71; 330; wage discrimination; immigration; labor supply; informal incentives; minimum wage